1979
DOI: 10.1111/j.1559-1816.1979.tb02707.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Level of Challenge on Pressor and Heart Rate Responses in Type A and B Subjects1

Abstract: The present study examined the relationship between the Type A coronaryprone behavior pattern and the magnitude of cardiovascular response induced by varying levels of environmental challenge. In a 2 × 2 experimental design, Type A and B (noncoronary‐prone) subjects (n= 80) were randomly assigned to either high or low challenge instructional conditions for both the cold pressor (CP) and a choice reaction time task (RT). Overall, across both tasks, Type A subjects responded with greater systolic blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1
1

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(58 citation statements)
references
References 36 publications
5
51
1
1
Order By: Relevance
“…This finding was consistent with those of previous research [4][5][6][7][8][9][10][11], This increased level of physiological arousal in type As relative to type Bs was at variance with the data pertaining to selfreported physical symptoms and state anxi ety. Viewed in the context of their greater HR and SBP change, the lower anxiety and physical symptom report, and particularly the lower heart-racing report by type As, sup ports previous findings of their tendency to underreport physical and emotional symp toms [6][7][8][11][12][13].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding was consistent with those of previous research [4][5][6][7][8][9][10][11], This increased level of physiological arousal in type As relative to type Bs was at variance with the data pertaining to selfreported physical symptoms and state anxi ety. Viewed in the context of their greater HR and SBP change, the lower anxiety and physical symptom report, and particularly the lower heart-racing report by type As, sup ports previous findings of their tendency to underreport physical and emotional symp toms [6][7][8][11][12][13].…”
Section: Discussionsupporting
confidence: 81%
“…The type A behaviour pattern (TABP) [1], which is characterized by the well-defined attributes of excessive competitive drive, hostility, aggressiveness and a sense of time urgency [2], has been shown to relate to cor onary heart disease (CHD) in both prospec tive studies and retrospective ones [3], The mechanisms by which the TABP is linked with CHD arc as yet incompletely under stood but central to the argument is the gen eral hypothesis that at least some situations, particularly those perceived by the individ ual as threatening and competitive, have the capacity to challenge those with the TABP in such a way as to cause exaggerated physio logical activation [4][5][6][7][8][9][10][11]. The risk for CHD implied by such physiological responses has been argued to be exacerbated by type As' tendency to fail to recognize or at least re port these symptoms of physical distress [ 12,13], thus making As less likely to seek medi cal attention or to take other forms of reme dial action.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even after disease is manifest, A-B differences in cardiovascular reactivity can still be observed (17,18), suggesting that these mechanisms remain active and may possibly influence the course of the disease and subsequent clinical outcomes.…”
Section: Davids Krantzetalmentioning
confidence: 95%
“…This requires participants to place their hand in cold water yielding heightened arousal and cardiovascular reactivity (e.g., Glass, McKinney, Hofschire, & Fedorko, 1990). Further, it has been shown that high-hostile individuals evidence greater cardiovascular reactivity (BP and HR) to the cold pressor task than low-hostile individuals (Dembroski, MacDougall, Herd, & Shields, 1979). More recently, Demaree and Harrison (1997) suggested that because stressful cardiovascular measures may tap right cerebrum activity, the effects of stress and arousal on hostile individuals may best be accounted for by right cerebrum reactivity.…”
mentioning
confidence: 99%